Demethylzeylasteral inhibits proliferation and metastasis of osteosarcoma cells by modulating the PI3K/AKT/Autophagy pathways - Xuhui Yuan; Jiayu Li; Bo Yu; Feng Cai; Binqi Chen; Jun Liu; Yuanxiang Peng; Duo Zeng; Qi Liao; Lang Liu (Journal of Bone Oncology)
Background: Osteosarcoma (OS) remains a highly aggressive malignancy with limited treatment options, necessitating the discovery of novel therapeutic agents. Demethylzeylasteral (DEM), a compound previously shown to exert anti-tumor properties in several malignancies, has not been sufficiently explored for its potential in OS treatment. Purpose: This study focused on the anti-tumor properties of DEM on OS cells as well as the potential mechanisms. Methods: OS cell lines (MG63 and 143B) were exposed to varying concentrations of DEM, followed by assessment of diverse cell functions. RNA sequencing was implemented to identify the molecular pathways affected by DEM exposure. The mechanistic underpinnings of DEM’s action were also studied via a series of assays. Additionally, the therapeutic potential was validated utilizing xenograft models. Results: DEM evidently repressed OS cell proliferation in a dose- and time-dependent fashion, arrested cells in G2/M phase, and facilitated apoptosis through the modulation of the BCL2/BAX ratio. Furthermore, DEM suppressed cell migration and invasion by reversing EMT-related protein expression. RNA sequencing revealed that DEM primarily affected autophagy-related pathways, particularly through the PI3K/AKT signaling. DEM treatment led to an elevation in ROS generation and enhanced autophagic activity, as demonstrated by elevated LC3B puncta formation and autophagy-related protein expression. In vivo, DEM effectively suppressed tumor growth while showing a favorable safety profile. Conclusion: This study provides comprehensive evidence that DEM exerts potent anti-tumor properties in OS via the PI3K/AKT pathway, highlighting the significance of DEM as a therapeutic candidate for OS.